PEMANFAATAN MEDIA SOSIAL SEBAGAI PENDORONG PEMASARAN GLOBAL UNTUK MENINGKATKAN PRODUKSI (Studi Kasus Media Sosial TikTok) - Suhairi; Raudatun Sumi; Lestari Perdana Putri; Miftahul Jannah Hasibuan; Rediansyah Saranan (Jurnal Nusantara Berbakti, 2023)
The Internet is of great help in many areas of life, including government, business, commerce, and the economy. The development and progress of the internet is now also marked by the progress of social media in society. Social media is now increasingly penetrated into various aspects of everyday life. As well as advocating for causes (educational, social, religious, environmental, health, and so on), as well as promoting and marketing certain goods or services, social media can be used for various things as it develops. Therefore, as a businessman and company, the use of social media is also something that is effectively implemented in marketing activities and then becomes one of the factors for increasing industry and production. So this research is present to see how the use of social media as a driving force for global marketing to increase promotion, in this study the focus of research is social media tikTok.